Algae-Derived Polysaccharides Promote Growth Performance by Improving Antioxidant Capacity and Intestinal Barrier Function in Broiler Chickens - Liu, Wen-Chao; Guo, Yan; Zhao, Zhi-Hui; Jha, Rajesh; Balasubramanian, Balamuralikrishnan (Frontiers in Veterinary Science, 2020)
This study aimed to determine the efficacy of dietary algae-derived polysaccharides (ADP) from Enteromorpha on growth performance, intestinal morphology, intestinal permeability, antioxidant capacity in serum, liver, and intestinal mucosa of broilers. A total of 396 day-old male chicks were randomly assigned to six dietary treatments containing 0, 1,000, 2,500, 4,000, 5,500, and 7000 mg ADP/kg basal diet in a 35 d feeding trial. Increasing dietary ADP levels increased average daily gain (quadratic, p < 0.01) and feed conversion ratio (linear, p < 0.05) in the overall study period but did not affect (p > 0.05) average daily feed intake. Dietary ADP supplementation increased total superoxide dismutase (T-SOD) (linear, p < 0.05) and serum catalase (CAT) activities (quadratic, p < 0.05) in liver and decreased (p < 0.05) malondialdehyde (MDA) content in serum and liver at d 21 and 35. At d 21, dietary ADP increased (linear, p < 0.05) the villus height of duodenum, jejunum, and ileum, and the villus width and villus surface area of the duodenum. At d 35, dietary ADP enhanced (linear, p < 0.05) the villus height of duodenum and ileum and the villus height to crypt depth ratio of the duodenum. Moreover, an improvement in the villus surface area of the duodenum and ileum was observed in ADP fed birds at d 35. At d 21, there was a linear increase (p < 0.05) in T-SOD activity in jejunal and ileal mucosa and CAT activity in ileal mucosa but a linear decrease of MDA concentrations in the mucosa of duodenum, jejunum, and ileum with increasing levels of ADP. At d 35, increasing ADP levels significantly increased T-SOD activity in jejunal mucosa and reduced MDA contents in duodenal mucosa (linear, p < 0.05). Additionally, dietary ADP decreased (quadratic, p < 0.05) serum D-Lactic acid at d 21, and reduced (linear, p < 0.05) serum diamine oxidase activities at d 21 and 35. In conclusion, dietary ADP exerted beneficial effects on growth performance, antioxidant capacity, and gut health in broilers. These findings provided new insights into the potential application of ADP as natural growth promoters in broilers.